Transcranial direct current stimulation (tDCS) in behavioral and food addiction: a systematic review of efficacy, technical, and methodological issues - Sauvaget, Anne; Trojak, Benoît; Bulteau, Samuel; Jiménez-Murcia, Susana; Fernández-Aranda, Fernando; Wolz, Ines; Menchón, José M.; Achab, Sophia; Vanelle, Jean-Marie; Grall-Bronnec, Marie (Frontiers in Neuroscience, 2015)
Objectives. Behavioral addictions (BA) are complex disorders for which pharmacological and psychotherapeutic treatments have shown their limits. Non-invasive brain stimulation, among which transcranial direct current stimulation (tDCS), has opened up new perspectives in addiction treatment. The purpose of this work is to conduct a critical and systematic review of tDCS efficacy, and of technical and methodological considerations in the field of BA. Methods. A bibliographic search has been conducted on the Medline and ScienceDirect databases until December 2014, based on the following selection criteria: clinical studies on tDCS and BA (namely eating disorders, compulsive buying, Internet addiction, pathological gambling, sexual addiction, sports addiction, video games addiction). Study selection, data analysis and reporting were conducted according to the PRISMA guidelines. Results. Out of 402 potential articles, seven studies were selected. So far focusing essentially on abnormal eating, these studies suggest that tDCS (right prefrontal anode / left prefrontal cathode) reduces food craving induced by visual stimuli. Conclusions Despite methodological and technical differences between studies, the results are promising. So far, only few studies of tDCS in BA have been conducted. New research is recommended on the use of tDCS in BA, other than eating disorders.